Analisis Pengaruh Keadilan Perpajakan, Sistem Perpajakan, Pemahaman Perpajakan Dan Sanksi Perpajakan Terhadap Persepsi Pajak Mengenai Perilaku Penggelapan Pajak (Tax Evasion) Di Kpp Pratama Teluk Betung - Yulia, Rasti; Hertia (LPPM STIE KRAKATAU, 2017)
The purpose of this study is to determine the influence of business partnership coaching on increasing productivity of small industry companies and other factors that affect productivity. The method used in this research is survey method and kuisoner with linear regression analysis using SPSS. Based on the results of this study it can be concluded that 46.7% increase in business productivity is influenced by business coaching while the remaining 53.3% is influenced by other factors.